Integration of FPGA RDMA into the ATLAS readout with FELIX in High Luminosity LHC. (1st January 2023) - Vasile, M.; Martoiu, S.; Boukhadida, N.; Stoicea, G.; Micu, P.; Dumitru, A.; Ulmamei, A.; Hobincu, R.; Iordache, C.
Abstract: The FELIX system is used to interface the front-end electronics and the commodity hardware in the server farm of the ATLAS experiment. FELIX is using RDMA through RoCE to transmit data from its host servers to the Software Readout Driver using off-the-shelf networking equipment. In the current version of FELIX, RDMA communication is implemented using software on both ends of the links. Improvements of the data throughput as part of the High Luminosity LHC upgrade, by implementing RDMA support in the front-end FELIX FPGA, have been tested. A version of FELIX that uses the FPGA implementation of RDMA is being proposed and demonstrated.